Commercial Manufacture of Halaven®: Chemoselective Transformations En Route to Structurally Complex Macrocyclic Ketones - Austad, Brian C.; Calkins, Trevor L.; Chase, Charles E.; Fang, Francis G.; Horstmann, Thomas E.; Hu, Yongbo; Lewis, Bryan M.; Niu, Xiang; Noland, Thomas A.; Orr, John D.; Schnaderbeck, Matthew J.; Zhang, Huiming; Asakawa, Naoki; Asai, Naoki; Chiba, Hiroyuki; Hasebe, Takashi; Hoshino, Yorihisa; Ishizuka, Hiroyuki; Kajima, Takashi; Kayano, Akio; Komatsu, Yuki; Kubota, Manabu; Kuroda, Hirofumi; Miyazawa, Mamoru; Tagami, Katsuya; Watanabe, Tomohiro (Synlett, 2013)
The evolution of the synthesis of Halaven® (E7389, INN eribulin mesylate) from a medicinal chemistry process to the execution of the final process on pilot scale is described. The completion of the synthesis of Halaven® from C1–C13 ester and C14–C35 sulfone alcohol involves a series of chemo-, regio-, and stereoselective transformations. Furthermore, a high-dilution macrocyclization presented a number of challenges for industrial-scale manufacture (throughput, processing time, and side reactions). This paper describes studies at Eisai leading to an understanding, optimization, and control of the chemistry that realized the reproducible commercial production of Halaven®.
Keywords: carbanions; coupling; drugs; ketones; macrocycles